2020
DOI: 10.1111/jcmm.15822
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of potential prognostic biomarkers in metastatic skin cutaneous melanoma by bioinformatics analysis

Abstract: Skin cutaneous melanoma (SKCM) is the deadliest cancer among commonly encountered skin malignant tumours due to its extreme aggressiveness and dissemination. 1 At present, SKCM is usually diagnosed in the late grades of metastatic tumours, which could drive patients to a poor response to the therapeutic strategies. 2 Therefore, we need to explore the potential biomarkers and therapeutic targets to improve the diagnosis and therapy of invasive melanoma. The malignant transformation of melanocytes is a multistep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Some scholars ( 50 ) believe that the upregulation of SPRR is often accompanied by damage to the normal structure of the stratum corneum, which affects the function of epithelial barrier and leads to the decrease of skin hydration, antioxidation, wound healing, drug sensitivity and anti-infection ability. At the same time, some studies have shown that the expression of SPRR1B is down-regulated in metastatic melanoma ( 51 ). The results of TMA also confirmed that IGF2BP3 was significantly up-regulated in melanoma, and also confirmed that SPRR1B was significantly down-regulated in metastatic cancer before tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars ( 50 ) believe that the upregulation of SPRR is often accompanied by damage to the normal structure of the stratum corneum, which affects the function of epithelial barrier and leads to the decrease of skin hydration, antioxidation, wound healing, drug sensitivity and anti-infection ability. At the same time, some studies have shown that the expression of SPRR1B is down-regulated in metastatic melanoma ( 51 ). The results of TMA also confirmed that IGF2BP3 was significantly up-regulated in melanoma, and also confirmed that SPRR1B was significantly down-regulated in metastatic cancer before tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that SPRR1B is overexpressed in oral squamous cell carcinoma stem‐cell‐like cells, thereby affecting cell growth 22 . SPRR1B has also been identified as one of the predictive indicators for the prognosis of patients with pancreatic cancer 23 or metastatic transformation of melanoma 24 . In head and neck squamous cell carcinoma (HNSCC), SPRR1B affects HNSCC angiogenesis by targeting MDA‐9/Syntenin, thereby affecting tumor invasion and differentiation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies constructed protein-protein interaction (PPI) networks to identify hub genes in melanoma. Sheng et al constructed a PPI network to analyze differentially expressed genes (DEGs) from the Gene Expression Omnibus (GEO) database [35]. The study identified DGS3, DSC3, PKP1, EVPL, IVL, FLG, SPRR1A, and SPRR1B as potential biomarkers that predict the metastases of cutaneous melanoma [35].…”
Section: Current Bioinformatics In Melanoma Risk Assessementmentioning
confidence: 99%
“…Sheng et al constructed a PPI network to analyze differentially expressed genes (DEGs) from the Gene Expression Omnibus (GEO) database [35]. The study identified DGS3, DSC3, PKP1, EVPL, IVL, FLG, SPRR1A, and SPRR1B as potential biomarkers that predict the metastases of cutaneous melanoma [35]. Another study constructed a PPI network from melanoma gene expression data from UCSC Xena and GEO and found FOXM1, EXO1, KIF20A, TPX2, and CDC20 as genes associated with reduced overall survival [36].…”
Section: Current Bioinformatics In Melanoma Risk Assessementmentioning
confidence: 99%